Purchase Decision through Product Innovation and Service Quality Analysis - Hutabarat, Zuhri Saputra (Jurnal Ilmiah Dikdaya, 2022)
This study aims to find the effect of product innovation and service quality on purchasing decisions on Batik Zhorif in DanauTeluk Jambi District, Seberang City. This research is a descriptive analytical research to examine causal or correlational phenomena, with a population of 125 consumers and 67 samples. The results of the analysis show that there is an effect of product innovation on purchasing decisions of 0.628 and the effect of service quality on purchasing decisions of 0.647. And there is a joint or simultaneous influence between the influence of product innovation and service quality on purchasing decisions of 0.693. As for the two variables studied, the product innovation variable is more dominant in influencing purchasing decisions.